Strengthening Islamic Financial Literacy among Majelis Taklim in Seberang Ulu II District, Palembang - Soediro, Achmad; kusumawardani, media; aspahani; Maysaroh, Watim (Sricommerce: Journal of Sriwijaya Community Services, 2026)
This community engagement initiative addresses the socio-economic and religious challenges faced by residents of 16 Ulu Urban Village, Seberang Ulu II District, Palembang (Badan Pusat Statistik Kota Palembang, 2024)(Kecamatan SU II, 2024). Drawing on field observations, semi-structured interviews with community leaders and the management of the Salam Insaniyah Foundation, and corroborated by official district-level data, the study identifies two interrelated structural issues: persistently low levels of Islamic financial literacy and the limited involvement of women in sharia-based financial decision-making. The findings align closely with the extant literature in three critical respects: (1) inadequate Islamic financial literacy as a key determinant of economic precarity among low-income households; (2) the strategic role of women’s empowerment as household-level economic agents within the sharia economic framework; and (3) the urgent need for systematic integration between sharia literacy initiatives, Islamic microfinance institutions, and social finance instruments particularly zakat and waqf to advance social justice and financial inclusion. Overall, the intervention is empirically grounded, contextually responsive, and demonstrates strong potential to foster long-term outcomes, including the development of sharia conscious communities and economically as well as spiritually resilient micro, small, and medium enterprises (MSMEs).